2010
DOI: 10.1111/j.1600-6143.2010.03242.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin and MPA, But Not CsA, Impair Human NK Cell Cytotoxicity Due to Differential Effects on NK Cell Phenotype

Abstract: Cyclosporin A (CsA), rapamycin (Rapa) and mycophenolic acid (MPA) are frequently used for GVHD prophylaxis and treatment after allogeneic stem cell transplantation (SCT). As NK cells have received great interest for immunotherapeutic applications in SCT, we analyzed the effects of these drugs on human cytokinestimulated NK cells in vitro. Growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 33 publications
(11 reference statements)
7
47
0
Order By: Relevance
“…Hence, it is known that immature CD56 bright and NKG2A þ CD56 dim NK cells have a higher propensity to produce cytokines upon exogenous cytokine stimulation compared with more mature NK cells [1,7,10,[12][13][14]20,25,27]. Alternatively, cyclosporine A is also known to reduce target celleinduced IFN-g production and enhance cytokineinduced IFN-g production by human NK cells [32]. However, the latter conclusion remains controversial because another study showed that cyclosporine A did not alter cytokine production by NK cells [33].…”
Section: Discussionmentioning
confidence: 96%
“…Hence, it is known that immature CD56 bright and NKG2A þ CD56 dim NK cells have a higher propensity to produce cytokines upon exogenous cytokine stimulation compared with more mature NK cells [1,7,10,[12][13][14]20,25,27]. Alternatively, cyclosporine A is also known to reduce target celleinduced IFN-g production and enhance cytokineinduced IFN-g production by human NK cells [32]. However, the latter conclusion remains controversial because another study showed that cyclosporine A did not alter cytokine production by NK cells [33].…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, CsA pharmacodynamic effect on NK cells is distinct and allows NK cell cytotoxicity, 41 whereas it is impaired by MMF [42][43][44] or MTX. [45][46][47] Moreover, calcineurin inhibitors are the only immunosuppressive agents exerting their action by inhibiting interleukin-2 production.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, TNF-a has been linked to increased replication of CMV (45). In vitro, TNF-a directly stimulates the CMV immediate-early promoter and can dramatically increase malignant transformations by triggering the NF-kB transcriptional activator, thus contributing to the immune failure seen in various malignancies (46). Our experimental evidence supports this possibility: intracellular cytokine production in NK cells differed quite notably between both OLT groups with de novo tumors, with NK cells of 2C + expressing mainly TNF-a and those of 2C 2 produced more IFN-g. Popivanova et al (47) showed that blocking TNF-a reduces carcinogenesis of this solid colorectal tumor, whereas IFN-g levels, as mediated by NK cells, predict long-term survival in patients with gastrointestinal stromal tumors after treatment with imatinib mesylate (48).…”
Section: Discussionmentioning
confidence: 99%